Cathodes pinpoints for the next generation of energy storage devices: the LiFePO4 case study - Beatriz Arouca Maia; Beatriz Moura Gomes; Antonio Nuno Guerreiro; Raquel Miriam Santos; Maria Helena Braga (JPhys Materials, 2024)
There are still essential aspects regarding cathodes requiring a comprehensive understanding. These include identifying the underlying phenomena that prevent reaching the theoretical capacity, explaining irreversible losses, and determining the cut-off potentials at which batteries should be cycled. We address these inquiries by investigating the cell’s capacity and phase dynamics by looking into the transport properties of electrons. This approach underlines the crucial role of electrons in influencing battery performance, similar to their significance in other materials and devices such as transistors, thermoelectrics, or superconductors. We use lithium iron phosphate LFP as a case study to demonstrate that understanding the electrochemical cycling behavior of a battery cell, particularly a Li//LFP configuration, hinges on factors like the total local potentials used to calculate chemical potentials, electronic density of states (DOS), and charge carrier densities. Our findings reveal that the stable plateau potential difference is 3.42 V, with maximum charge and minimum discharge potentials at 4.12 V and 2.80 V, respectively. The study illustrates the dynamic formation of metastable phases at a plateau voltage exceeding 3.52 V. Moreover, we establish that determining the working chemical potentials of elements like Li and Al can be achieved by combining their workfunction and DOS analysis. Additionally, we shed light on the role of carbon black beyond conductivity enhancement. Through Density functional theory (DFT) calculations and experimental methods involving scanning Kelvin probe (SKP) and electrochemical analysis, we comprehensively examine various materials, including Li, C, Al, Cu, LFP, FePO _4 , Li _0.25 FePO _4 , polyvinylidene fluoride, and Li _6 PS _5 Cl. The insights derived from this study, which solely rely on electrical properties, have broad applicability to all cathodes and batteries. They provide valuable information for efficiently selecting optimal formulations and conditions for cycling batteries.